2003
DOI: 10.1063/1.1586692
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state charge transfer dynamics in systems of aromatic adsorbates on TiO2 studied with resonant core techniques

Abstract: Resonant core spectroscopies are applied to a study of the excited electron transfer dynamics on a low-femtosecond time scale in systems of aromatic molecules ͑isonicotinic acid and bi-isonicotinic acid͒ adsorbed on a rutile TiO 2 (110) semiconductor surface. Depending on which adsorbate state is excited, the electron is either localized on the adsorbate in an excitonic effect, or delocalizes rapidly into the substrate in less than 5 fs ͑3f s ͒ for isonicotinic acid ͑bi-isonicotinic acid͒. The results are obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
70
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 69 publications
13
70
1
Order By: Relevance
“…Charge transfer on the sub-3 fs timescale from the LUMO+2 of the biisonicotinic acid molecule into the conduction band of the underlying TiO 2 (110) conduction band has been experimentally measured using RPES and is supported by sub-5 fs timescales measured for isonicotinic acid on the same surface. 6,18 However, in our measurements there is no evidence of the channels identified as participator decay processes (elastic scattering and vibronic coupling) being depleated for the monolayer for which fs charge transfer out of the LUMO+2 has been shown to occur. Enhancements of the Rayleigh (elastic) line previously observed in the RIXS of isolated molecules are typically understood in terms of core-excitonic states leading to an enhanced probability of the originally excited electron filling the corehole, resulting in elastic participator decay.…”
Section: Resultscontrasting
confidence: 38%
See 1 more Smart Citation
“…Charge transfer on the sub-3 fs timescale from the LUMO+2 of the biisonicotinic acid molecule into the conduction band of the underlying TiO 2 (110) conduction band has been experimentally measured using RPES and is supported by sub-5 fs timescales measured for isonicotinic acid on the same surface. 6,18 However, in our measurements there is no evidence of the channels identified as participator decay processes (elastic scattering and vibronic coupling) being depleated for the monolayer for which fs charge transfer out of the LUMO+2 has been shown to occur. Enhancements of the Rayleigh (elastic) line previously observed in the RIXS of isolated molecules are typically understood in terms of core-excitonic states leading to an enhanced probability of the originally excited electron filling the corehole, resulting in elastic participator decay.…”
Section: Resultscontrasting
confidence: 38%
“…The LUMO+1 and LUMO+2 states however, lie well above the conduction band edge of the TiO 2 (110) surface and have been shown through RPES to undergo ultra-fast charge transfer into the surface on the low femtosecond timescale. 6,18 Integrating over the participator region of the RIXS for both the multilayer and monolayer as a function of absorption energy, we compare the relative intensities of the participator channel for each unoccupied molecular orbital compared to the x-ray absorption (XAS).…”
Section: Resultsmentioning
confidence: 99%
“…Bi-isonicotinic anchors to the surface through the deprotonated carboxylic groups, and as such all four oxygen atoms in the molecule are equivalent [9][10][11]. Attachment of the molecule via the deprotonated carboxylic group is a common feature of aromatic carboxylic acid molecules adsorbed on TiO 2 [15][16][17][22][23][24]. In the O 1s core-level spectrum we therefore expect to see just two features, one due to the molecule and the other due to the TiO 2 (1 1 0) surface.…”
Section: Adsorption Of Bi-isonicotinic Acidmentioning
confidence: 94%
“…Any loss of integrity in the unoccupied molecular orbitals during the experiment through beam damage could completely undermine the RPES observations. Our previous studies of the adsorption and charge transfer dynamics of bi-isonicotinic acid adsorbed on a variety of surfaces [6][7][8][10][11][12][15][16][17] successfully eliminated molecular damage through continuously scanning the incident beam across the surface to maintain the exposure below a well characterized limit. This technique is also used in the present study, in which we focus our attention on the nature of the damage to the adsorbed bi-isonicotinic acid molecule.…”
Section: Introductionmentioning
confidence: 97%
“…It has been envisaged that combination of porphyrin with fullerenes can lead to the development of advance organic material, which has potential application in light-harvesting devices [12], molecular magnets [13] and porous metal-organic framework [14,15]. Many fullerene-porphyrin supramolecular systems have been proposed to achieve high-performance photovoltaic devices [16]. Very recently Imahori et al has reported porphyrin-fullerene linked system as artificial photosynthetic mimics [17].…”
Section: Introductionmentioning
confidence: 98%